Quantum Mechanics Inside Quantum Communication and Quantum Bit Error Rate(QBER) - Nayek, Susmita; Roy, Utpal (International Journal of Computer Sciences and Engineering, 2025)
The quantum cryptography has changed the landscape of the conventional cryptography theory and the field of security itself. The Quantum cryptography differs from the classical cryptography in the sense that data and the information are kept secret by the properties of quantum mechanics without importing any extra formulation. In case of classical cryptography the security is based on the conjecture difficulty of factoring and computing a special mathematical function. The first Quantum Key Distribution (QKD) protocol was proposed by C H Bennet and Brassard in 1984[1](BB84). In course of time many variants of QKD protocols have been proposed, all are basically based more or less in the same principle. In this paper role and the beauty of the Quantum Mechanics behind the QKD protocol have been unfolded and explained. The pros-and cons of the protocol have been analyzed in details. The quality of the QKD protocol is measured through a factor called QBER (Quantum Bit Error Rate). The bit error rate is an essential phenomena during the transmission of quantum bit along the quantum channel. Both quantum mechanical and mathematical analysis of QBER have been discussed in the paper. An empirical formula for QBER has been proposed too